Arthroscopic Fixation of Symptomatic Meso-Type Os Acromiale: Technical Note - Quen Oak Tang; Sherif Elnikety (Case Reports in Orthopedics)
Symptomatic Os acromiale can cause pain, impingement, and reduced range of movement. Disruption of the syndesmosis can result in significant pain and functional impairment; this may occur after trauma. Symptomatic Os acromiale is treated by either excision or fixation. Fixation via open technique is the mainstay of surgical intervention; however, recently, arthroscopic methods were used. In this technical note, we discuss the modification for all arthroscopic Os acromiale fixation; the fixation screws are introduced in anteroposterior fashion, employing the advances in orthopaedic fixation devices. Arthroscopic fixation is not widely adopted, possibly due to availability of implants and perceived difficult learning curve. We report this technique and demonstrate reproducibility with excellent results.